Independent Curriculum (Kurikulum Merdeka)-Based PAI Learning Management at Private Islamic Religious Universities (PTKIS) - Amet Amet; Yuli Marlina; Luthfi Yasykur; Uus Ruswandi (EDUTEC : Journal of Education And Technology, 2024)
The purpose of this study is to describe the implementation of the Merdeka curriculum in Islamic religious higher education at Islamic University of Jakarta. We focus on competency-based approaches, active learning, and learning methods that support the development of practical skills. Learning methods such as project-based learning, problem-based learning and collaborative learning are in line with the philosophy of the Merdeka curriculum. The method used is a qualitative research approach. The sample of this study is Jakarta Islamic University as PTKIS located in Jakarta. Data analysis is performed in several phases including a) data transcription, b) data classification, c) data validation, and d) data interpretation. The findings of this study indicate that the implementation of the Merdeka curriculum in PTKI faces challenges and progress. To achieve the goals of the Merdeka curriculum - to create more relevant learning that meets the needs of a dynamic world of work - better understanding of instructors, more partners and alignment in the practice of values. is required.